Head trauma from traffic accidents - Toniato e Silva, Vitor; Argote Gonzales, Javier (International Journal of Neurology, 2025)
Background: Traumatic brain injury (TBI) from road traffic accidents is a major cause of morbidity and mortality in adults. This systematic review evaluates whether early surgical intervention combined with intensive hospital management improves clinical outcomes in these patients. Material and methods: A systematic literature review was conducted focusing on studies from the last ten years. Selected studies included adult patients with severe TBI due to traffic accidents, treated with early surgery and intensive care. Outcomes analyzed included mortality, neurological sequelae, and long-term quality of life. Results: Most studies found that early surgical decompression within hours of trauma, along with intensive monitoring, significantly reduced mortality rates and improved functional neurological recovery and quality of life. Fewer secondary complications were also observed. Conclusion: Early surgical treatment combined with intensive hospital management is an effective strategy to improve outcomes in patients with TBI due to road traffic accidents. Systematic implementation and future prospective studies are recommended